2020
DOI: 10.1017/s0022377820001270
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic entropy-based measures of distribution function non-Maxwellianity: theory and simulations

Abstract: We investigate kinetic entropy-based measures of the non-Maxwellianity of distribution functions in plasmas, i.e. entropy-based measures of the departure of a local distribution function from an associated Maxwellian distribution function with the same density, bulk flow and temperature as the local distribution. First, we consider a form previously employed by Kaufmann & Paterson (J. Geophys. Res., vol. 114, 2009, A00D04), assessing its properties and deriving equivalent forms. To provide a quantitative u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…The first class employs both collisionless and weaklycollisional and Gkeyll simulations of a single current sheet that undergoes symmetric anti-parallel magnetic reconnection. In the collisionless case, we find that and a separate PIC code P3D (Zeiler et al 2002), adopted in Liang et al (2020), provide consistent and qualitatively similar results. Although the and Gkeyll simulations are very similar in their choice of parameters, there are small differences we make note of in the subsequent discussion.…”
Section: Simulations Setupsupporting
confidence: 60%
See 1 more Smart Citation
“…The first class employs both collisionless and weaklycollisional and Gkeyll simulations of a single current sheet that undergoes symmetric anti-parallel magnetic reconnection. In the collisionless case, we find that and a separate PIC code P3D (Zeiler et al 2002), adopted in Liang et al (2020), provide consistent and qualitatively similar results. Although the and Gkeyll simulations are very similar in their choice of parameters, there are small differences we make note of in the subsequent discussion.…”
Section: Simulations Setupsupporting
confidence: 60%
“…proposed by Liang et al (2020). Here, 𝑠 M, 𝛼 (𝒓, 𝑡) is the entropy density evaluated using the equivalent Maxwellian distribution function 𝑔 𝛼 (𝒓, 𝒗, 𝑡) associated with the VDF 𝑓 𝛼 (𝒓, 𝒗, 𝑡), given by…”
mentioning
confidence: 99%
“…In addition, characterizing entropy yield insights on magnetic self-organization (a means of counteracting entropy production) and plasma phase transitions [23]. Despite these motivations, there are relatively few studies that attempt to directly measure kinetic entropy or related proxies in first-principles simulations of plasmas [e.g., 18,[23][24][25][26][27]. This is due not only to numerical issues (such as high resolution demands), but also conceptual issues such as how to meaningfully normalize entropy [18].…”
Section: Introductionmentioning
confidence: 99%
“…At present various papers have considered the non-Maxwellianity of particle distributions in both simulations and observations [Greco et al, 2012;Valentini et al, 2016;Chasapis et al, 2018;Perri et al, 2020;Liang et al, 2020]. These studies have focused on plasma turbulence in Earth's magnetosheath and magnetic reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results showed that ion non-Maxwellianity was spatially non-uniform and was associated with strong currents and temperature anisotropy [Greco et al, 2012;Valentini et al, 2016]. Similarly, electron non-Maxwellianity was found to increase the electron diffusion region (EDR) and separatrices of magnetic reconnection [Liang et al, 2020]. In kinetic simulations the background distributions, such as in modeling of magnetosheath turbulence and magnetic reconnection, are assumed to be Maxwellian.…”
Section: Introductionmentioning
confidence: 99%